Հայաստանի Հանրապետության լոգիստիկ համակարգում երթուղիների օպտիմալացման արդյունքում բեռնափոխադրման ծախսերի կրճատման էկոնոմետրիկ գնահատում - Ղլիջյան, Տիգրան (ՀԱԱՀ հիմնադրամ)
Географическое положение Республики Армения, отсутствие прямого выхода к морю, блокада границ с востока и запада, а также ежегодно сокращающиеся объемы сельскохозяйственного производства препятствуют экономическому развитию. Исходя из этого особое внимание уделяется эксплуатации новых инфраструктур в логистической системе, снижению расходов на логистику за счет эффективного управления грузоперевозками. В рамках исследования была поставлена задача посредством эконометрических расчетов определить экономическую рентабельность строящихся в республике дорожных инфраструктур, путем применения экономико-математических моделей снизить логистические издержки и увеличить объемы грузоперевозок, что значительно повысит роль Армении в международной торговле․ The logistics system of the Republic of Armenia is currently undergoing a phase of active development. However, from a logistical standpoint, the country faces a number of significant challenges, including an unfavorable geographic location, declining agricultural production volumes, blockaded borders to the east and west, the absence of direct access to the sea, and consequently, some of the highest transportation costs in the region. These factors present serious barriers to Armenia’s economic growth and regional competitiveness. Thus, the current article aims to assess the economic viability of proposed road infrastructure projects in Armenia through practical econometric modeling. The results of these economic-mathematical calculations yield multifactor indicators that can serve as a preliminary justification for the construction of new logistics infrastructure in the coming years. Such infrastructure development is anticipated to enhance Armenia’s role in international trade and act as a strategic driver for the multi-sectoral growth of the country›s provinces, reinforcing their significance and integration within the broader regional framework.
Keywords: Ագրարային տնտեսագիտություն և ագրոբիզնես